The interstitium at the developing nephron in the fetal kidney during advanced pregnancy - a microanatomical inventory - Will W. Minuth (SpringerOpen, 2022)
Abstract Background A series of noxae can evoke the termination of nephron formation in preterm and low birth weight babies. This results in oligonephropathy with severe consequences for health in the later life. Although the clinical parameters have been extensively investigated, little is known about the initial damage. Previous pathological findings indicate the reduction in width of the nephrogenic zone and the lack of S-shaped bodies. Current morphological investigations suggest that due to the mutual patterning beside the forming nephron, also its structural neighbors, particularly the interjacent interstitium, must be affected. However, beside the findings on integrative and mastering functions, systematic microanatomical data explaining the configuration of the interstitium at the developing nephron in the fetal kidney during advanced pregnancy is not available. Therefore, this work explains the typical features. Results The generated data depicts that the progenitor cells, nephrogenic niche, pretubular aggregate, and mesenchymal-to-epithelial transition are restricted to the subcapsular interstitium. During the proceeding development, only the distal pole of the renal vesicles and comma- and S-shaped bodies stays in further contact with it. The respective proximal pole is positioned opposite the peritubular interstitium at the connecting tubule of an underlying but previously formed nephron. The related medial aspect faces the narrow peritubular interstitium of a collecting duct (CD) ampulla first only at its tip, then at its head, conus, and neck, and finally at the differentiating CD tubule. The lateral aspect starts at the subcapsular interstitium, but then it is positioned along the wide perivascular interstitium of the neighboring ascending perforating radiate artery. When the nephron matures, the interstitial configuration changes again. Conclusions The present investigation illustrates that the interstitium at the forming nephron in the fetal kidney consists of existing, transient, stage-specific, and differently far matured compartments. According to the developmental needs, it changes its shape by formation, degradation, fusion, and rebuilding.